2007
DOI: 10.1109/pes.2007.385827
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Short Circuit Performance of Split-Winding Transformer Using Coupled Field-Circuit Approach

Abstract: Abstract-The split-winding arrangement requires special short-circuit design considerations. During short-circuit conditions, there is a considerable distortion of the leakage field, which in turn produces high axial short-circuit forces. This paper deals with the computation and analysis of electromagnetic forces in windings of split-winding transformers. A nonlinear-transient field-circuit coupled finite element model is used to simulate the split-winding transformer. A 70-MVA, three-phase, 220/6.9/6.9-kV sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Several authors have developed formulations to compute the average and maximum values of these forces in round-core power transformers. Both the analytical formulations [9,10,12] and the 3D numerical analysis Finite-Element-Method analysis [15,20,21] obtained similar force patterns within the windings of a power transformer.…”
Section: Electromagnetic Forces In Transformer Windingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have developed formulations to compute the average and maximum values of these forces in round-core power transformers. Both the analytical formulations [9,10,12] and the 3D numerical analysis Finite-Element-Method analysis [15,20,21] obtained similar force patterns within the windings of a power transformer.…”
Section: Electromagnetic Forces In Transformer Windingsmentioning
confidence: 99%
“…These electromagnetic forces present as radial and axial forces [9][10][11]. Analysis of electromagnetic forces within a power-transformer is well established [9][10][11][12][13][14][15][16][17][18][19]. It was shown that such forces are potential sources for damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweep Frequency Response Analysis (SFRA) is a powerful method for the detection and diagnosis of defects in the active part of power transformer which can deliver valuable information about the mechanical as well as the electrical changes in the windings parameters. Kulkarni and Kumbhar (2007) have computed the force distribution due to short-circuit current in a splitwinding transformers using Finite Element Analysis (FEA). Faiz et al (2008) have analyzed the radial and axial electromechanical forces developed by the inrush and short circuit currents using 2D and 3D Finite Element Method (FEM) models.…”
Section: Introductionmentioning
confidence: 99%